Overview and status of estuarine microphytobenthos ecological research in South Africa. Issue 1 (2nd January 2018) - Dalu, T; Adams, JB; Taylor, JC; Bate, GC; Nunes, M; Froneman, PW; Wasserman, RJ
Abstract : This article presents a historical overview of estuarine microphytobenthos (MPB) research in South Africa published over the period 1950 to the present, highlighting major milestones, challenges and estuarine management problems, as well as future research needs within the South African context. The studies that were covered comprise peer-reviewed books and journal articles on relevant research conducted in any estuarine environment during the period reviewed. There was a general increase in MPB research outputs over the decades, from only two publications in the 1950s, to over 20 outputs between 2010 and the present. Whereas the MPB studies in South Africa cover a broad spectrum of themes, the research priorities in these works have changed from taxonomically biased studies to those of ecologically based research. Research in the 1950s and 1960s was exclusively taxonomic in nature, with the first ecological investigation incorporating MPB being produced in the 1970s. By the 1980s, ecological studies dominated the research outputs and this trend has persisted to the present. The 1990s and 2000s saw the rise of research into the role of fresh water as a driver of MPB dynamics, whereas the period 2010 to the present saw an increase in more diverse ecological themes, ranging from an autecological investigation to food-web studies and the assessment of multiple drivers of MPB dynamics. However, the majority of studies have focused on either diatoms or estimates of overall MPB biomass. Moreover, there is a regional underrepresentation that runs broadly along biogeographic lines, with the bulk of the work having been conducted in the warm-temperate and subtropical zones of South Africa. Challenges and future research needs for the region are outlined, as is the need to expand MPB research to include other aspects of the biology and ecology of this flora.